(untitled) (Homoeopathy for All, 2025)
Allergic rhinitis (commonly called hayfever) is an inflammation or irritation of the mucous membranes that line the nose. Common symptoms include sneezing; a stuffy or runny nose; itchy eyes, nose and throat;and watery eyes. The patient may havea nasal voice; breathe noisily; snore; feel chronically tired; have a poorappetite; feel nauseated; have frequent headaches; and, have somedifficulty hearing and smelling.